Archaeological Perspectives on the Transmission and Transformation of Culture in the Eastern Mediterranean - Clarke, J. (Council for British Research in the Levant, 2005)
The eastern Mediterranean was the centre of trade for many centuries, sitting at the junction of what are now Europe, Asia and Africa. It was the place where exotic produce and products could be traded or exchanged for things that had their origins perhaps thousands of miles away. But wherever trade takes place, a similar exchange of ideas, technology and culture also occurs. This book presents thirty papers on this very subject, looking at the ways in which we can measure the transmission of culture, and how this transmission varied across time and space.